Effect of silymarin pretreatment on the bioavailability of domperidone in healthy human volunteers - Yamsani, Shravan Kumar; Yamsani, Madhusudan Rao (Drug metabolism and drug interactions, 2014)
The aim of this study was to investigate the effect of silymarin pretreatment on domperidone oral bioavailability in humans. The rats were pretreated with silymarin for 7 days. The transport of domperidone across the rat intestine (duodenum, jejunum, ileum, and colon) was studied by using everted and non-everted sac methods. Samples were collected at preset time points and replaced with buffer. The drug content in the samples was estimated. The first part of the study included oral administration of 10 mg domperidone tablet alone, and blood was sampled from the antecubital vein. The second part of the study was conducted after a washout period of 2 weeks. Five hundred milligrams of silymarin was administered twice daily for 6 days. On day 7, one tablet each of 10 mg domperidone and 500 mg silymarin were administered concomitantly. In the everted sac and non-everted sac study with silymarin pretreatment, domperidone transport increased from the duodenum, jejunum, ileum, and colon. The silymarin pretreatment increased the bioavailability of domperidone. There was a statistically significant difference in the pharmacokinetic parameters C , , AUC , and AUC The significant difference in absorption of domperidone on pretreatment with silymarin is due to the inhibition of P-glycoprotein and CYP3A. Silymarin, which inhibits CYP3A4, should be contraindicated for domperidone.